The Empowerment of MSME Actors in Rindu Hati Tourism Village through Training on Digital Marketing Utilization during the Covid-19 Pandemic. - Hayu, Rina (LPPM Universitas PGRI Adi Buana Surabaya, 2022)
Since the COVID-19 pandemic disaster in early 2020 hit the whole world, the tourism sector in Rindu Hati Tourism Village has experienced a decline, this can be seen in the impact, namely the closure of tourist routes and tourist areas in Rindu Hati Village. Changes in lifestyle and economic order during the pandemic have affected New Normal behavior, such as shifting business patterns, resilience and efficiency, shifting industrial structures, shifting people's behavior, industrial revolution 4.0, as well as digital ecosystems that are connected between sectors. This New Normal will result in a shift in economic patterns with minimal face-to-face meetings or the Less Contact Economy, which is marked by hyperconnectivity between humans through Information and Communication Technology (ICT). Therefore, the service activity using this training method is aimed empowerment of MSME actors in the village of homesickness through digital marketing by using the Youtap Indonesia trade application, which is considered capable of accommodating the Less contact Economy, especially with consumers. It is evident that 85% of service participants feel important and are seriously interested in using the Youtap Indonesia application as a means of promoting and selling their MSME products.